On back: In honor of the celebration of Peter Kropotkin on the occasion of his 70th birthday. Speakers Alexander Berkman, H. Jaxson, Vincent St.John, Emma Goldman, Dr.K. Fornberg Wm. Nathanson
On back: In honor of the celebration of Peter Kropotkin on the occasion of his 70th birthday. Speakers Alexander Berkman, H. Jaxson, Vincent St.John, Emma Goldman, Dr.K. Fornberg Wm. Nathanson.